Automated Scalpel Patterning of Solution Processed Thin Films for Fabrication of Transparent MXene Microsupercapacitors. Issue 44 (4th October 2018) - Salles, Pol; Quain, Evan; Kurra, Narendra; Sarycheva, Asia; Gogotsi, Yury
Abstract: A simple and generic strategy is proposed to pattern thin films deposited by a solution processable route. A soft approach based on an automated scalpel technique is developed to engrave thin films in a single step for sculpting functional planar devices. MXenes—the emerging family of 2D transition metal carbides and nitrides—combine metallic conductivity and hydrophilicity, enabling solution processing of transparent conducting electrodes (TCEs) under ambient conditions. Scalable dip coating is employed to process titanium carbide, Ti3 C2, MXene thin films with excellent optoelectronic properties, achieving electrical Figure of merit up to 14. Automated scalpel engraving is adopted to fabricate transparent and semi‐transparent MXene microsupercapacitors in a single step, hitherto not reported. Combining TCE and pseudocapacitive characteristics, MXene devices show excellent capacitive storage capabilities at high rates, without the aid of external metal current collectors. This technique allows for maskless patterning of solution processed thin films without losing intrinsic physicochemical properties and can be extended to fabricate heterostructured hybrid devices out of solution processable materials. Abstract : Coplanar microdevices are fabricated by scraping patterns on MXene thin films directly using an automated scalpel technique.